AIN and role of steroids - Yaqub, Soniya (Pakistan Journal of Kidney Diseases, 2022)
BACKGROUND: Acute interstitial nephritis (AIN) is a potentially reversible, but under-diagnosed cause of acute kidney injury. The role of steroids in the management of drug-induced AIN is debatable. There is scarcity of data on clinical characteristics of drug induced AIN, and role of steroids and its impact on renal outcomes from the developing countries. METHODS: We performed a retrospective study of patients with biopsy proven AIN over a period of 11 years. The main outcomes were recovery of renal function (Early (≤3 weeks) or Late (>3 weeks) and hemodialysis (HD) dependence at 12 weeks.